Імітаційне моделювання руху транспортного робота - Ащепкова, Наталія Сергіївна; Капера, Сергій Сергійович (НТУ "ХПІ", 2015)
Розглянуто імітаційне моделювання транспортного робота на основі Lego Mindstorms NХТ 2.0. Визначено склад системи керування та особливості конструкції шасі моделі транспортного робота. Існуюча елементна база дозволяє здійснювати пошук об'єкту, транспортування та виштовхування його за робочу зону. Додаткова умова вибору стратегії руху–обмеженість робочої зони. Реалізовані три стратегії руху: пошук кеглів з поверненням до центру, переміщення по спіралі, «Танок у колі». Оптимальна стратегія обрана за критерієм швидкодії.

Use of a set Lego Mindstorms NХТ 2.0 allows to design models of various robots. This article discusses the the imitating modeling of the transport robot based on Lego Mindstorms NXT. Are determined structure of a control system and feature of a design the chassis of model of the transport robot. The existing element base allows to carry out search to object, transportation and pushing out it for a working zone.. Hardware and the soft-ware of a control system allow to carry out search of object, transportation and pushing out it for a working zone. The element base provides an opportunity of creation of control systems of a different level of complexity. The imitating modeling of movements of real designs of robots allows to choose strategy of movement by the specified criterion of an optimality. Three strategy of movement are realized: search of size with returning to the centre, moving on a spiral, " Dance in a circle ". The optimum strategy is elected by criterion of speed. Additional condition of a choice of strategy of movement-limitation of a working zone.
Imitating modeling of movement of the transport robot
Keywords: модель робота; стратегія руху; критерій оптимальності; швидкодія; transport robot; working zone; strategy of movement; criterion of an optimality; speed